Homocystein Levels in Migraine Patients - Sari, Suna Ozlem Mutlu; Hiz, Fazilet; Bilge, Semra; Celebi, Arif (My University, 2011)
Objective: Migraine is a common chronic disease, characterised by the recurrence of disabling headache attack, and autonomic nervous system dysfunction. Integrated neurovascular theories have been appropriated in the migraine physiopathology. Vascular changes are responsible for the formation of migraine symptoms. Migraine association is remarkable in young cerebral ischemia cases. Hyperhomocysteinemia is an independent risk factor for vascular diseases such as thrombosis, atherosclerosis, myocardial infarct and ischemic stroke. High homocysteine levels in some patients with this pathology have been determined. Therefore, we investigated hyperhomocysteinemia, which is a probable causal factor of the relationship between migraine and ischemic stroke in patients with migraine with or without aura.